Water oxidation intermediates on iridium oxide electrodes probed by in situ electrochemical SHINERS. Issue 7 (2nd January 2020) - Saeed, Khezar H.; Forster, Mark; Li, Jian-Feng; Hardwick, Laurence J.; Cowan, Alexander J.
Abstract : Shell-isolated nanoparticle-enhanced Raman spectroscopy (SHINERS) is applied to the study of a state-of-the-art water oxidation electrocatalyst, IrO x, during oxygen evolution. Abstract : Shell-isolated nanoparticle-enhanced Raman spectroscopy (SHINERS) is applied to the study of a state-of-the-art water oxidation electrocatalyst, IrO x, during oxygen evolution. The excellent sensitivity allows for in situ detection of surface intermediate species during cyclic voltammetry. Features in the Raman spectrum are correlated with the redox behaviour of the electrode, demonstrating a way to study the mechanisms of electrocatalytic water splitting using equipment available in most laboratories.